Living with Contradiction: Examining the Worldview of the Jewish Settlers in Hebron - Røislien, Hanne Eggen (International Journal of Conflict and Violence (IJCV), 2007)
In the West Bank city of Hebron the Israeli-Palestinian conflict still overshadows all activities. Despite the tension, friction, and violence that have become integral to the city’s everyday life, the Jewish Community of Hebron is expanding in numbers and geographical extent. Since the Six Day War, the community has attracted some of the most militant groups among the settlers in the West Bank, responsible for severe violence against Palestin- ians, including harassment, car bombs, and attempts to blow up the Dome of the Rock mosque itself. Why do the members of the Jewish Community of Hebron wish to live and raise their children in such a violent setting? Using a series of interviews with members of the Jewish Community of He- bron and related settler communities in the period 2000–05, the article examines the ways the Jewish Community legitimizes its disputed presence. It reveals a deep religious belief, blended with intense distrust of and hatred toward the Palestinian population.